Pengaruh Leverage, Ukuran Perusahaan Dan Likuiditas Terhadap Corporate Social Responsibility Disclosure Dengan Profitabilitas Sebagai Variabel Moderasi - Kartika Wulandari; Yani Suryani; Ahmad Sani (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2022)
The purpose of this study was to examine the effect of corporate social responsibility, firm size, and leverage on firm value with profitability as a moderating variable. This type of research is quantitative research with causalty approach. The population used in this study is property and real estate companies listed on the Indonesia Stock Exchange ini 2016-2020. The sample in this study used purposive sampling which is 23 companies and the observation 5 years in a row so it counts 115. Data collection techniques in this study using documentation techniques. The data analysis technique in this study usesmultiple linear regression.The results of this study prove that corporate social responsibility has an effect on firm value, firm size and leverage have no effect on firm value, profitability can moderate the relationship of corporate social responsibility, company size and leverage to firm value in Property and Real Estate Companies Listed on the Indonesia Stock Exchange 2016-2020.